Children at Familial Risk of Dyslexia: Practical Implications from an At-Risk Study - Muter, V; Snowling, M (2009)
A longitudinal study was conducted of 50 at-risk poor readers who were seen at four assessment points between the ages of three years and nine months and 12-13 years. This provided a wealth of data about the incidence of reading problems, the course of developmental relationships among language and literacy skills and the factors that influence outcome (including risk and protective factors and co-morbid difficulties). The practical implications of this study are considered for the management of poor readers; including identifying children at-risk of dyslexia, assessing and teaching poor readers, addressing co-occurring difficulties, capitalising on compensatory or protective factors and providing emotional support. © 2009 The Author. Journal compilation © 2009 Association for Child and Adolescent Mental Health.